FEATURES OF MYOCARDIAL REMODELING, VEGETATIVE REGULATION, AND PSYCHOSOMATIC STATUS IN PATIENTS WITH DIFFERENT PHENOTYPES OF HEART FAILURE AND ATRIAL FIBRILLATION - N. M. Kulaіets (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
In order to substantiate the peculiarities of myocardial remodeling, the parameters of echocardiography of the heart, the state of vegetative regulation, and the psychosomatic status of patients with various forms of atrial fibrillation were studied. 90 patients aged 45-65 were examined. All patients were divided into groups according to the presence of chronic heart failure: Group I - patients with heart failure with atrial fibrillation (permanent or persistent form), (n=50). II group - patients without heart failure with atrial fibrillation, (n=40). III – control group: 36 practically healthy people. All patients underwent electrocardiography, echocardiography, Holter ECG monitoring, determination of heart rhythm variability, and psychological testing. According to the results of the study, it was established that the presence of atrial fibrillation, even without pronounced structural pathology of the heart, signs of heart failure, is a factor that worsens the temporal and spectral indicators of heart rate variability: the indicators of sympatho-parasympathetic modulation, parasympathetic activity are significantly reduced. In patients with chronic heart failure and atrial fibrillation, dilatation of the left atrium, an increase in end-diastolic and end- systolic dimensions, end-diastolic and end-systolic volumes of the left ventricle, stroke volume, and a decrease in the ejection fraction are most often observed, which indicates the processes of myocardial remodeling. According to the results of psychological testing, patients with chronic heart failure have pronounced personal and situational anxiety, an increased level of depression, which is a predictor of further progression of heart failure. Key words: chronic heart failure, atrial fibrillation, heart rate variability, left ventricular ejection fraction.